Peculiarities of the administrative functions regulation at the metallurgical enterprises - Artem Shevchenko (Cхід, 2013)
The necessity of developing number standards for the managers on the basis of the of management functions regulation for various levels of management is proved. The consistency and structure of management functions at the metallurgical enterprises are investigated. The correlation of general and specific functions for the further consideration in calculating the number standards for manager is defined. A scientific and methodical approach to dealing with the types of work by the possibility of labor input rationing during the determination of the standards for the top management number.